Peran Dukun dalam Pemilihan Kepala Desa Pasir Putih - Hatimah, Andi Husnul; Tamma, Sukri; Yunus, Ariana (Palita: Journal of Social Religion Research, 2023)
The role of shamans in the 2019 local elections is the focus of this study. In addition, the issue of the shaman's position in village elections is discussed in this paper. This study uses a qualitative method. This study relies on primary and secondary data for its findings. The Library Research method was used for data collection purposes in this study. The writer collects information from scientific writings, such as thesis diaries and documents. The author processes the information he collects according to the requirements of the analysis. The research findings show that residents still believe a certain kind of shaman exists. This kind of shaman is used to illustrate when village head elections are held. In regional head elections, especially village head elections, village head candidates develop a belief system to shape social and political attitudes. Whereas shamans rely on mystical reasoning as the foundation of their abilities and take advantage of the mystical devices they have, shamans are used as a guide to progress, what percentage of victory is desired and as a political network for electing village heads and instilling influence over residents so that they get the mass support that shamans have for their political goals.